The Brain Oxylipin Profile Is Resistant to Modulation by Dietary n‐6 and n‐3 Polyunsaturated Fatty Acids in Male and Female Rats. Issue 1 (29th January 2019) - Ferdouse, Afroza; Leng, Shan; Winter, Tanja; Aukema, Harold M.
Abstract: Oxylipins are bioactive lipids formed by the monooxygenation of polyunsaturated fatty acids (PUFA). Eicosanoids derived from arachidonic acid (ARA) are the most well‐studied class of oxylipins that influence brain functions in normal health and in disease. However, comprehensive profiling of brain oxylipins from other PUFA with differing functions, and the examination of the effects of dietary PUFA and sex differences in oxylipins are warranted. Therefore, female and male Sprague–Dawley rats were provided standard rodent diets that provided additional levels of the individual n‐3 PUFA α‐linolenic acid (ALA), eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA), or the n‐6 PUFA linoleic acid (LNA) alone or with ALA (LNA + ALA) compared to essential fatty acid‐sufficient control diets. Oxylipins and PUFA were quantified in whole brains using HPLC‐MS/MS and GC, respectively. Eighty‐seven oxylipins were present at quantifiable levels: 51% and 17% of these were derived from ARA and DHA, respectively. At the mass level, ARA and DHA oxylipins comprised 81–90% and 6–12% of total oxylipins, while phospholipid ARA and DHA represented 25–35% and 49–62% of PUFA mass, respectively. Increasing dietary n‐3 PUFA resulted in higher levels of oxylipins derived from their precursor PUFA; otherwise, the brain oxylipin profile was largely resistant to modulation by diet. Approximately 25% of oxylipins were higher in males, and this was largely unaffected by diet, further revealing a tight regulation of brain oxylipin levels. These fundamental data on brain oxylipin composition, diet effects, and sex differences will help guide future studies examining the functions of oxylipins in the brain.